Strategi CSR PT Mifa Bersaudara Dalam Meningkatkan Layanan Kesehatan Gratis Kepada Masyarakat Gampong Paya Baro, Meureubo, Kabupaten, Aceh Barat - Mutiara Safitri,; Risma Dedek,; Remayati,; Rahmatullah,; Yuliana,; Sopar, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
West Aceh, as a coal-producing region, faces challenges in developing public health services. Data shows that there is still unequal access to health services in rural areas of Aceh, both in terms of infrastructure and the availability of medical personnel (Ministry of Health of the Republic of Indonesia, 2021). This study aims to determine the implementation of PT Mifa Bersaudara's CSR strategy in improving free health services to the community of Gampong Paya Baro, Mereubo District, West Aceh Regency. This study used qualitative methods through a descriptive approach. Data analysis techniques included literature studies, direct observation, interviews, and analysis of theories from previous studies relevant to the issues discussed. The results of this study indicate that the frequency of implementation, reaching three to four times annually, demonstrates the company's dedication to providing much-needed additional healthcare access. The most striking and distinguishing feature of this program is the comprehensive facilities provided. The company ensures that all community needs are met, from quality health checks to the provision of free, nutritious food. This eliminates potential obstacles, ensuring residents can focus on their health. The study concludes that PT Mifa Bersaudara's CSR strategy in providing services is very optimal and smooth. The company provides comprehensive healthcare facilities to the Gampong Paya Baro community, thus positively impacting their health.